Improve Children's Early Reading Skills Through Picture Word Card Media - Nuryati, Nuryati; Rizadatun, Rita (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2023)
This article aims to examine the problem of early reading skills in group B students in Kutilang Kindergarten, Kramatwatu District, Serang Regency. This article aims to determine the improvement of the initial reading skills of group B students in Kutilang Kindergarten after using picture word card media using Classroom Action Research which consists of two cycles each cycle held as many as two meetings which include planning, implementation, observation and reflection. So it can be concluded that the reading ability of group B children of Kutilang Kindergarten can be improved through picture word card activities